Preparation method of micron-sized flaky manganese dioxide and application of micron-sized flaky manganese dioxide in oxygen evolution of alkaline electrolyzed water
By treating KMnO4 at 200°C to 1000°C and preparing micron-scale thin MnO2 through multi-step reaction, the existing OER catalysts have been solved, and efficient and stable catalyst preparation is achieved, which is suitable for large-scale applications.
Patent Information
- Application Number
- CN202411873538.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, the preparation of oxygen precipitation reaction (OER) catalysts is expensive, the catalyst activity is low and the process is complex, making it difficult to achieve large-scale application.
KxMnO2 was prepared by reacting KMnO4 at 200°C to 1000°C, and micron-scale flake MnO2 was prepared by heating of hydrochloric acid, nitric acid proton exchange and tetrabutyl ammonium hydroxide peeling steps, and used as a catalyst in alkaline electrolytic oxygen evolution.
It realizes the efficient preparation of micron-scale thin sheet MnO2, with high activity and stability, is suitable for large-scale production, and provides a new idea of designing efficient and stable electrocatalysts.
Smart Images

Figure CN119822409A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation and application of manganese dioxide, and in particular to a method for preparing micron-sized flaky manganese dioxide and its application in oxygen evolution in alkaline water electrolysis. Background Art
[0002] As one of the most critical reactions in solar energy conversion, the direct photo(electro)chemical decomposition of water to generate H2 and O2 has attracted widespread attention. The development of efficient oxygen evolution reaction (OER) catalysts is the key to solving the problem of solar fuel production to store renewable energy in the form of chemical fuels.
[0003] Currently, the most robust and efficient OER catalysts are noble metal oxides (e.g., RuO2 and IrO2). However, their scarcity and high cost make them unfeasible for large-scale applications. Therefore, it is very important to develop cheap and highly active OER catalysts. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for preparing micron-sized flaky manganese dioxide and its application in alkaline water electrolysis for oxygen evolution, aiming to solve the problems of expensive preparation cost, low catalyst activity and complex process in related technologies.
[0005] To achieve the above object, the present invention provides a method for preparing micron-sized flake MnO2, comprising:
[0006] KMnO4 is reacted at 200℃~1000℃ to obtain K x MnO2, and prepared into K x MnO2 aqueous solution; the K x The concentration of the MnO2 aqueous solution was 7.9 g / 250 mL H2O.
[0007] To the K x Hydrochloric acid is added to a MnO2 aqueous solution and heated to obtain bulk potassium-type birnessite; wherein the heating temperature is 80°C; and the molar concentration of the hydrochloric acid is 2.2-2.6 mol / L.
[0008] The blocky potassium-type birnessite is added into a nitric acid solution for reaction, and the solid matter is separated to obtain hydrogenated birnessite.
[0009] Then, the hydrogenated birnessite is added into a tetrabutylammonium hydroxide solution for exfoliation to obtain the micron-sized flake MnO2.
[0010] According to an embodiment of the present application, the reaction temperature of KMnO4 is 200°C, 400°C, 600°C, 800°C or 1000°C.
[0011] According to an embodiment of the present application, the nitric acid solution comprises nitric acid and water, wherein the molar concentration of the nitric acid is 0.05 to 0.15 mol / L.
[0012] According to an embodiment of the present application, the x The steps of adding hydrochloric acid to a MnO2 aqueous solution and heating to obtain bulk potassium-type birnessite include:
[0013] The hydrochloric acid was added dropwise at a rate of 1 mL / min. x The reaction mixture was added to an aqueous MnO2 solution and the reaction temperature was maintained at 80°C. After the hydrochloric acid was completely added, heating was continued at 80°C for 0.5 hours.
[0014] According to an embodiment of the present application, the step of adding the blocky potassium-type birnessite to a nitric acid solution for reaction and separating the solid matter therein comprises:
[0015] The blocky potassium-type birnessite is reacted with the nitric acid solution under stirring for 2 days to perform proton exchange, and the solid is separated by centrifugation and washed with water until the pH value is 6-7 and then dried.
[0016] According to an embodiment of the present application, the stripping step further includes:
[0017] The exfoliated components were washed with isopropanol, ethanol and water and then dried to obtain micron-sized flake MnO2.
[0018] According to an embodiment of the present application, an application of the micron-sized flake MnO2 as described above in oxygen evolution by alkaline water electrolysis includes:
[0019] An electrode pair is used to electrolyze an alkaline aqueous solution, wherein the electrode pair includes a working electrode, and a conductive solution in the working electrode includes carbon black and the micron-sized flake-shaped MnO2.
[0020] According to an embodiment of the present application, the conductive solution includes isopropanol and tetrafluoroethylene solution, in which 6 mg of micron-sized flake MnO2, 5 mg of carbon black and 50 μL of polytetrafluoroethylene solution are dispersed in every 1 mL of isopropanol.
[0021] According to an embodiment of the present application, the electrode pair further includes a counter electrode and a reference electrode.
[0022] In the step of electrolyzing the alkaline aqueous solution using the electrode pair, the electrolysis parameters include: a current density of 10 mA / cm 2 ; Scanning voltage is 1.0~2.0V vs.RHE; Scanning rate is 10mV / s.
[0023] According to an embodiment of the present application, the mass fraction of the polytetrafluoroethylene solution is 5%; the polytetrafluoroethylene solution contains polytetrafluoroethylene and anhydrous ethanol.
[0024] The present invention provides a method for preparing micron-sized thin-sheet manganese dioxide. KMnO4 is reacted at 200°C to 1000°C to obtain K x MnO2, and then, by adding hydrochloric acid and heating to obtain blocky potassium birnessite, wherein the temperature is controlled to adjust the concentration of Mn vacancies, and then a nitric acid solution is added to undergo proton exchange to obtain hydrogenated birnessite, which is then dispersed in a tetrabutylammonium hydroxide solution to form a stable colloid, and aggregated micron-sized flake MnO2 is obtained by solid-liquid separation.
[0025] The prepared micron-sized flake MnO2 has different sizes at different heating temperatures, and its size can be adjusted by controlling the decomposition temperature, thus achieving the performance optimization of micron-sized flake MnO2. The defective micron-sized flake MnO2 exhibits high activity and stability in the reaction of oxygen evolution in alkaline water electrolysis. The preparation method is simple, easy to operate, and suitable for large-scale production. This study provides new ideas for the design of efficient and stable electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0027] Figure 1 TEM images of MnO2 prepared by KMnO4 at different heating temperatures (0-1000℃).
[0028] Among them, 0℃(a); 400℃(b); 600℃(c); 800℃(d); 1000℃(e); the statistical proportion of the number of hole sizes (f);
[0029] Figure 2 Electron energy loss (EELS) diagram of micron-scale flake MnO2 sample prepared by heating KMnO4 at 1000℃.
[0030] Figure 3 High-resolution transmission electron microscopy (HRTEM) image of a micron-sized flake MnO2 sample prepared by heating KMnO4 at 1000°C;
[0031] Figure 4The X-ray diffraction (XRD) patterns of MnO2 prepared by KMnO4 at different heating temperatures (0-1000°C);
[0032] Figure 5 The Raman spectra of MnO2 prepared by KMnO4 at different heating temperatures (0-1000℃);
[0033] Figure 6 Atomic force microscopy (AFM) image of a micron-sized flake MnO2 sample prepared by heating KMnO4 at 1000°C (a), and a layer thickness image of MnO2 (b);
[0034] Figure 7 Polarization curves (a), Tafel (b), and stability after CV1000th (c) of micron-sized flake MnO2 prepared by KMnO4 at different heating temperatures (0-1000℃) in alkaline (1.0mol / L KOH) electrolyte.
[0035] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0038] To achieve the above object, the present invention provides a method for preparing micron-sized flake MnO2, comprising:
[0039] Step S100: react KMnO4 at 200°C to 1000°C to obtain K x MnO2, and prepared into K x MnO2 aqueous solution; the K x The concentration of the MnO2 aqueous solution was 7.9 g / 250 mL H2O.
[0040] In this step, for example, KMnO4 is heated at 200°C to 1000°C for 5 hours under air conditions at a heating rate and a cooling rate of 1°C / min to obtain a pyrolysis product, and then the pyrolysis product is washed with distilled water for multiple times and dried in an oven to obtain K x MnO2.
[0041] The reaction temperature is 200°C to 1000°C. For example, the reaction temperature is 200°C to 400°C, 400°C to 600°C, 600°C to 800°C, 800°C to 1000°C. More specifically, the reaction temperature is 400°C, 600°C, 800°C, or 1000°C.
[0042] Step S200: Send the K x Hydrochloric acid is added to a MnO2 aqueous solution and heated to obtain bulk potassium-type birnessite; wherein the heating temperature is 80°C; and the molar concentration of the hydrochloric acid is 2.2-2.6 mol / L.
[0043] In this step, illustratively, the heating temperature is controlled to 80°C, and HCl is added dropwise to the K at a rate of 1 mL / min. x After the hydrochloric acid is completely added to the MnO2 aqueous solution, continue to heat at 80°C for 0.5 hours, then stand at 50°C for 15 hours, wash with distilled water, vacuum filter, and dry the filtered product in an oven to obtain blocky potassium-type birnessite.
[0044] Among them, K x The MnO2 aqueous solution was passed through 7.9 g K x It is prepared by adding MnO2 into 250 mL of water.
[0045] The massive potassium-type birnessite is manganese dioxide doped with potassium and oxygen vacancies.
[0046] Step S300: adding the blocky potassium-type birnessite into a nitric acid solution for reaction, separating the solid matter therein, and obtaining hydrogenated birnessite.
[0047] In this step, illustratively, the step of separating the solid matter comprises:
[0048] The blocky potassium-type birnessite is reacted with the nitric acid solution under stirring for 2 days to perform proton exchange, and the solid is separated by centrifugation and washed with water until the pH value is 6-7 and then dried.
[0049] The proton exchange is that nitric acid reacts with bulk potassium-type birnessite to remove potassium from the bulk potassium-type birnessite.
[0050] Exemplarily, the nitric acid solution comprises nitric acid and water; the molar concentration of the nitric acid is 0.05 to 0.15 mol / L.
[0051] Also illustratively, the product is separated by centrifugation, washed with water to make the pH value of the supernatant liquid be 6-7, and then dried to obtain hydrogenated birnessite.
[0052] Step S400: adding the hydrogenated birnessite into a tetrabutylammonium hydroxide solution for exfoliation to obtain the micron-sized flake MnO2.
[0053] In this step, the stripping is performed at room temperature, for example. The stripping is performed by centrifuging at different speeds to remove tetrabutylammonium hydroxide.
[0054] In a specific embodiment, hydrogenated birnessite is added to a tetrabutylammonium hydroxide solution to form a suspension. After the suspension is shaken for 10 days, the tetrabutylammonium hydroxide is removed by centrifugation at 14,000 rpm for 30 minutes to aggregate and form a MnO2 precipitate.
[0055] The MnO2 precipitate was redispersed in 25 mL of water to form a colloidal suspension, and the residual tetrabutylammonium hydroxide was separated by centrifugation at 8000 rpm for 30 minutes.
[0056] In some embodiments, the stripping step further comprises:
[0057] The exfoliated components were washed with isopropanol, ethanol and water and then dried to obtain micron-sized flake MnO2.
[0058] In some embodiments, the reaction temperature of KMnO4 is 200° C., 400° C., 600° C., 800° C. or 1000° C. In some more specific embodiments, the optimal reaction temperature of KMnO4 is 1000° C., which can achieve good flake shape of the obtained micron-sized flake MnO2.
[0059] The present application also provides an application of the above-mentioned micron-sized flake MnO2 in oxygen evolution by alkaline water electrolysis, including:
[0060] An electrode pair is used to electrolyze an alkaline aqueous solution, wherein the electrode pair includes a working electrode, and a conductive solution in the working electrode includes carbon black and the micron-sized flake-shaped MnO2.
[0061] Exemplarily, the alkaline aqueous solution is a 0.1 mol / L KOH solution.
[0062] Exemplarily, the oxygen evolution reaction (OER) was studied by cyclic voltammetry (CV) and linear sweep voltammetry (LSV) using a CHI 660E electrochemical workstation at room temperature (22±2°C).
[0063] As another example, the electrolysis of water for oxygen evolution uses a three-electrode system, wherein the working electrode is the conductive solution dripped onto a 3 mm diameter glassy carbon electrode; wherein the loading amount is 1.62 mg / cm 2 .
[0064] The above-mentioned application of micron-sized flake MnO2 in oxygen evolution in alkaline water electrolysis is to adjust the concentration of Mn vacancies by controlling the decomposition temperature of KMnO4. The defective micron-sized flake MnO2 acts as a catalyst in oxygen evolution in alkaline water electrolysis, and shows good stability under continuous electrolysis conditions, and also shows high activity in electrocatalytic oxidation reactions.
[0065] In some embodiments, the conductive solution includes isopropanol and tetrafluoroethylene solution, in which 6 mg of micron-sized flake MnO2, 5 mg of carbon black and 50 μL of polytetrafluoroethylene solution are dispersed in every 1 mL of isopropanol.
[0066] Exemplarily, micron-sized flake MnO2 and carbon black are weighed and dispersed in isopropanol; after ultrasonic treatment for 3 minutes, polytetrafluoroethylene solution is added, and ultrasonic treatment is further performed for 60 minutes to obtain the conductive solution.
[0067] In some embodiments, the electrode pair further includes a counter electrode and a reference electrode.
[0068] Exemplarily, the counter electrode is a platinum wire; and the reference electrode is an Ag / AgCl electrode.
[0069] In the step of electrolyzing the alkaline aqueous solution using the electrode pair, the electrolysis parameters include: a current density of 10 mA / cm 2 ; Scanning voltage is 1.0~2.0V vs.RHE; Scanning rate is 10mV / s.
[0070] In some embodiments, the mass fraction of the polytetrafluoroethylene solution is 5%; the polytetrafluoroethylene solution contains polytetrafluoroethylene and anhydrous ethanol.
[0071] For further understanding of the present invention, examples are given below:
[0072] The chemical reagents and materials used in the present invention are as follows.
[0073] Platinum wire (purity 99.9%, diameter 1.0 mm), glassy carbon (GC) electrode, and Ag / AgCl electrode were obtained from Tianjin Yida Co., Ltd., China. Anhydrous ethanol was purchased from Shanghai Sinopharm Co., Ltd., China. Potassium permanganate (KMnO4), nitric acid (HNO3), tetrabutylammonium hydroxide (TBAOH), isopropanol, carbon black (Vulcan XC-72), and polytetrafluoroethylene (Nafion) were purchased from Shanghai McLean Biochemical Co., Ltd., China. Hydrochloric acid (36-38 wt%), KOH (≥85%), and other analytical grade reagents were obtained from Shanghai Aladdin Co., Ltd., China and used as received. Distilled water was used throughout the experiment.
[0074] Example 1
[0075] K x Preparation of MnO2: KMnO4 was heated to 400℃ at a rate of 1℃ / min under air conditions and maintained for 5 hours. The decomposition product was then washed with distilled water several times and dried to obtain K x MnO2.
[0076] Preparation of bulk birnessite (for ease of description, some bulk birnessite is referred to as bulk birnessite below): 7.9 g K x MnO2 was added to 250 mL of water, and 50.0 mL of 2.4 mol / L HCl was added dropwise at a rate of 1 mL / min at 80°C. After the addition was completed, the mixture was heated at 80°C for 0.5 hours. The solution was then allowed to stand at 50°C for 15 hours, washed with distilled water, vacuum filtered, and dried to obtain Bulk birnessite.
[0077] Preparation of hydrogenated birnessite (H / birnessite) (for ease of description, partially hydrogenated birnessite is referred to as H / birnessite below): 2 g Bulk birnessite was added to 500 mL 0.1 mol / L HNO3 solution, stirred for 2 days, centrifuged, washed with water to pH 6-7, and dried to obtain H / birnessite.
[0078] Preparation of micron-sized flake MnO2: 0.4 g H / birnessite was added to a solution consisting of 5.2 mL of TBAOH solution and 95 mL of water and exfoliated at room temperature.
[0079] Electrochemical performance test: Cyclic voltammetry and linear sweep voltammetry were performed on micron-sized flake MnO2 in 1 mol / L KOH electrolyte at room temperature (22±2°C). The electrode potential relative to Ag / AgCl was measured according to E RHE=E Ag / AgCl +0.098+0.059×pH converted to relative reversible hydrogen electrode potential.
[0080] Ag / AgCl was used as the reference electrode; platinum wire was used as the counter electrode; 20 μL of the conductive solution was dripped onto a 3 mm diameter glassy carbon electrode as the working electrode; the loading amount was 1.62 mg / cm 2 .
[0081] Example 2: The difference from Example 1 is that the heating temperature of KMnO4 is 600°C.
[0082] Example 3: The difference from Example 1 is that the heating temperature of KMnO4 is 800°C.
[0083] Example 4: The difference from Example 1 is that the heating temperature of KMnO4 is 1000°C.
[0084] Results and Discussion
[0085] 1. Characterization of micron-sized flake MnO2 prepared at different temperatures
[0086] The phase structure was analyzed by X-ray diffractometer (XRD, D8 advance diffractometer), and the Cu Ka irradiation wavelength λ was The morphology and microstructure were analyzed by high-resolution transmission electron microscopy (HR-TEM, JEOL, JEM2100F) and high-angle annular dark field scanning transmission electron microscopy (STEM-HAADF) equipped with electron energy loss spectroscopy (EELS). The chemical state of the constituent elements was analyzed by X-ray photoelectron spectroscopy (XPS, Shimadzu, AXIS Ultra SUPRA), and the binding energy was referenced to the C1s peak (284.8 eV) of amorphous carbon.
[0087] Transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HR-TEM), and high-angle annular dark field scanning transmission electron microscopy (STEM-HAADF) were used to characterize the micron-sized flake MnO2 prepared at different temperatures.
[0088] like Figure 1As shown, when the KMnO4 heating temperature is 0℃, the corresponding particle size is 65.83±10nm; when the KMnO4 heating temperature is 400℃, the corresponding MnO2 particle size is 92.00±20nm; when the KMnO4 heating temperature is 600℃, the corresponding MnO2 particle size is 209.67±30nm; when the KMnO4 heating temperature is 800℃, the corresponding MnO2 particle size is 2.68±0.5μm; when the KMnO4 heating temperature is 1000℃, the corresponding MnO2 particle size is 8.26±0.4μm. As the KMnO4 heating temperature increases, the size of the prepared MnO2 increases and is in the form of micron-sized flakes.
[0089] like Figure 2 EELS element mapping of the green rectangular area in the STEM-HAADF image is shown in Figure 2. ADF images were collected simultaneously, and the low-loss EELS and core-loss EELS showed perfectly matched signals in terms of image contrast, calculated thickness, Mn L-edge, and OK-edge. Figure 1 The holes seen in the TEM images are indeed the hollow structures of MnO2.
[0090] pass Figure 3 High-resolution transmission electron microscopy (HRTEM) and Figure 4 The X-ray diffraction (XRD) pattern of the MnO2 sample prepared at 1000°C was observed, and its micron-scale flake structure characteristics were clearly shown, among which, Figure 3 The results show that the interplanar spacing of the MnO2 sample prepared at 1000℃ is 0.205nm, which corresponds to the (401) crystal plane of MnO2 (JCPDScard no.43-1455). Figure 4 The results show that the (001) crystal plane intensity of the sample decreases significantly with the increase of preparation temperature, indicating that the crystallinity of the sample weakens. This is crucial for understanding the electrocatalytic performance of micron-sized flake MnO2.
[0091] like Figure 5 As shown in Figure 2, Raman spectroscopy analysis reveals the changes in the lattice structure of the sample as the preparation temperature increases. -1 、568cm -1 and 640cm -1 The peaks at 1 and 2 are hexagonal symmetry, Mn–O stretching vibration in the [MnO6] plane, and A 1g Symmetric stretching vibration characteristic peaks. When the preparation temperature exceeds 800℃, the three peaks of the obtained sample are red-shifted by 8cm -1 、7cm -1 and 10cm -1 These subtle structural changes can affect the electronic structure of the catalyst and thus its redox performance.
[0092] Figure 6 (a) is an atomic force microscope (AFM) image of a micron-sized flake MnO2 sample prepared by heating KMnO4 at 1000°C. Figure 6 (b) is a graph of the measured layer thickness of MnO2. It can be seen from the figure that the thickness of the MnO2 flakes prepared at 1000°C is 2.4-4.0nm, indicating that it is 3-6 layers of MnO2. The control of layer thickness is important for optimizing the performance of the catalyst because it is directly related to the distribution and density of the active sites of the catalyst.
[0093] 2. Catalytic activity, selectivity and stability of micron-sized flake MnO2 prepared at different temperatures in oxygen evolution in alkaline water electrolysis
[0094] like Figure 7 As shown in (a), it can be seen from the polarization curves that the micron-sized flake MnO2 prepared at different temperatures exhibits a relatively good electrocatalytic oxygen evolution effect in alkaline water electrolysis. Its catalytic performance and stability show excellent performance. This may be related to its unique two-dimensional morphology and moderate Mn valence composition.
[0095] Among them, the micron-sized flake MnO2 sample prepared at 600°C was heated at 10 mA / cm in 1 mol / L KOH electrolyte. 2 The best catalytic performance was shown at a current density of . This indicates that the micron-sized flake MnO2 sample has high stability and catalytic activity in practical applications and is expected to play an important role in industrial oxygen evolution reactions. Therefore, the micron-sized flake MnO2 can be used as a catalyst in oxygen evolution in alkaline water electrolysis.
[0096] From Figure 7 (b) It can be seen that the black arrow indicates the relationship between temperature and Tafel slope. When the KMnO4 heating temperature is between 0℃ and 400℃, the Tafel slope decreases as the temperature increases, while when the KMnO4 heating temperature is between 400℃ and 1200℃, the Tafel slope basically tends to be stable as the temperature increases. The red arrow indicates the relationship between temperature and 10mA / cm 2 The overpotential relationship under the current density. As the heating temperature of KMnO4 increases, the overpotential increases.
[0097] From Figure 7 The stability test results (c) show that under the operating conditions of scanning voltage 1.0-2.0V vs. RHE and scanning rate 10mV / s, the micron-scale flake MnO2 prepared at 800℃ and 600℃ still maintains high activity after scanning the same 1000th, indicating that it exhibits good stability under continuous electrolysis conditions.
[0098] The micron-sized flake MnO2 of the present application can be applied to the oxygen evolution reaction in alkaline water electrolysis. Experimental methods and results of using micron-sized flake MnO2 as a catalyst to enhance the oxygen evolution reaction. Micron-sized layered MnO2 was prepared by decomposing KMnO4 at 200°C to 1000°C, and the concentration of Mn vacancies was adjusted by controlling the temperature. The experimental results show that these defective MnO2 microsheets exhibit high activity and stability in electrocatalytic oxidation reactions. This study provides new ideas for the design of efficient and stable electrocatalysts.
[0099] In summary, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing micron-sized flake MnO2, characterized in that: include: KMnO4 is reacted at 200℃~1000℃ to obtain K x MnO2, and prepared into K x MnO2 aqueous solution; the K x The concentration of MnO2 aqueous solution is 7.9g / 250mL H2O; To the K x Add hydrochloric acid to the MnO2 aqueous solution and heat to obtain bulk potassium-type birnessite; wherein the heating temperature is 80° C.; the molar concentration of the hydrochloric acid is 2.2 to 2.6 mol / L; adding the blocky potassium-type birnessite into a nitric acid solution for reaction, separating the solid matter therein, and obtaining hydrogenated birnessite; Then, the hydrogenated birnessite is added into a tetrabutylammonium hydroxide solution for exfoliation to obtain the micron-sized flake MnO2.
2. The method for preparing micron-sized flake MnO2 according to claim 1, characterized in that: The reaction temperature of the KMnO4 is 200°C, 400°C, 600°C, 800°C or 1000°C.
3. The method for preparing micron-sized flake MnO2 according to claim 1, characterized in that: The nitric acid solution comprises nitric acid and water, wherein the molar concentration of the nitric acid is 0.05-0.15 mol / L.
4. The method for preparing micron-sized flake MnO2 according to claim 1, characterized in that: The K x The steps of adding hydrochloric acid to a MnO2 aqueous solution and heating to obtain bulk potassium-type birnessite include: The hydrochloric acid was added dropwise at a rate of 1 mL / min. x The reaction mixture was added to an aqueous MnO2 solution and the reaction temperature was maintained at 80°C. After the hydrochloric acid was completely added, heating was continued at 80°C for 0.5 hours.
5. The method for preparing micron-sized flake MnO2 according to any one of claims 1 to 4, characterized in that: The step of adding the blocky potassium-type birnessite to a nitric acid solution for reaction and separating the solid matter therein comprises: The blocky potassium-type birnessite is reacted with the nitric acid solution under stirring for 2 days to perform proton exchange, and the solid is separated by centrifugation and washed with water until the pH value is 6-7 and then dried.
6. The method for preparing micron-sized flake MnO2 according to claim 1, characterized in that: The stripping step further includes: The exfoliated components were washed with isopropanol, ethanol and water and then dried to obtain micron-sized flake MnO2.
7. An application of the micron-sized flake MnO2 as claimed in claims 1 to 6 in oxygen evolution by alkaline water electrolysis, characterized in that: include: An electrode pair is used to electrolyze an alkaline aqueous solution, wherein the electrode pair includes a working electrode, and the conductive solution in the working electrode includes carbon black and the micron-sized flake-shaped MnO2 described in any one of claims 1 to 6.
8. The use of micron-sized flake MnO2 in alkaline water electrolysis for oxygen evolution according to claim 7, characterized in that: The conductive solution includes isopropyl alcohol and tetrafluoroethylene solution; In the conductive solution, 6 mg of micron-sized flake MnO2, 5 mg of carbon black and 50 μL of polytetrafluoroethylene solution were dispersed in every 1 mL of isopropanol.
9. The use of micron-sized flake MnO2 in alkaline water electrolysis for oxygen evolution according to claim 7, characterized in that: The electrode pair also includes a counter electrode and a reference electrode; In the step of electrolyzing the alkaline aqueous solution using the electrode pair, the electrolysis parameters include: a current density of 10 mA / cm 2 ; Scanning voltage is 1.0~2.0V vs.RHE; Scanning rate is 10mV / s.
10. The use of micron-sized flake MnO2 in alkaline water electrolysis for oxygen evolution according to claim 8, characterized in that: The mass fraction of the polytetrafluoroethylene solution is 5%; the polytetrafluoroethylene solution contains polytetrafluoroethylene and anhydrous ethanol.